Politici de reformă în domeniul pensiilor - Mărginean, Ioan (Calitatea Vieții, 2007)
This essay is trying to briefly analyze the pension systems and their ways of organization, with the consequences for the achievement of their objective, namely providing reveniews for the population, after their withdrawall from the active life. We are also formulating proposals for further reforms concerning pensions, in Romania.